Enhanced Recovery After Surgery Reduces Postoperative Opioid Use and 90-Day Readmission Rates After Open Thoracolumbar Fusion for Adult Degenerative Deformity. (18th November 2021) - Adeyemo, Emmanuel A; Aoun, Salah G; Barrie, Umaru; Nguyen, Madelina L; Badejo, Olatunde; Pernik, Mark N; Christian, Zachary; Dosselman, Luke J; El Ahmadieh, Tarek Y; Hall, Kristen; Reyes, Valery Peinado; McDonagh, David L; et al.
Graphical Abstract: